Study of Effect of Adding Two Different Doses of Dexmedetomidine as an Adjuvant to Low Dose Bupivacaine in Saddle Block for Transurethral Resection of Prostate in Elderly Patients - Siddiq, Sana; Siddiq, Maimoona; Khaleeq, Saadia; Rehman, Abaid-ur-; Raza, Daniyal; Asad, Naila (Annals of King Edward Medical University, 2020)
Background: Transurethral Prostatectomy is most commonly carried out under spinal anesthesia in elderly males, it is of outmost importance to limit dose of LA and distribution of block in these patients to ensure stable hemodynamics. Objective: To compare the effects of adding two different doses of dexmedetomidine as an adjuvant with low dose bupivacaine in saddle block for TURP in elderly male population of Pakistan. Methods: The prospective, randomized, double-blind study was conducted on 75 patients of ASA Class I and II. They were randomly allocated into three groups. ml), Group II (n = 25) intrathecal bupivacaine 5 mg (1 ml) + dexmedetomidine 10 μg (1 ml), Group III (n = 25): intrathecal bupivacaine 5 mg (1 ml) + placebo (1 ml) administered intarthecally. The highest level and time to reach that level of sensory block, time of two-segment sensory regression, time of rescue analgesia and incidence of side effects were recorded at various intervals. Results: With comparable baseline and demographic features, median peak sensory block levels is T10 in group I and III whereas in group II it is T8. Time to reach maximal sensory level is 11.52±1.04 minutes in group I, 8.28±0.79 minutes in group II and13.92±.99 minutes in group III .Time required for two-segment regression being longest (189.80±26.47 vs. 128±15.1 and 64.04±8.08 (p=0.00) in group I and III respectively). Significant increase in time to first analgesic requirement is noted in group II (494.80±59.24 minutes) whereas in group I it is 356.60±55.47 minutes and in group III it is 179.92±25.44 minutes. Saddle block does not cause any significant hemodyamic changes as level of block is only restricted to perineal area, and similarly in my study no significant hemodynamic changes were recorded during anesthesia. Because of this, hemodynamic readings are not added in result. Conclusion: When dexmedetomidine is used in a dose of 10 µg as compared to 5 µg with low dose bupivacaine in saddle block, it hastens the onset and prolongs the effect of sub-arachanoid block, effectively reduces post-operative analgesic requirement and prolongs postoperative analgesic period. These effects could be achieved without any remarkable side effects.